A Literature Review of Green Human Resource Management for Gaining a Competitive Advantage - Johan Oscar Ong; Masydzulhak Djamil; Enny Ariyanto; Sugiyono Sugiyono (Universitas Mercu Buana, 2022)
Green human resource management (GHRM) plays an important role in organizations’ sustainable development strategies. However, there is still a research gap on the integration of available GHRM-related knowledge to gain a competitive advantage. Objectives: Thus, the purpose of this paper is to conduct a literature review on GHRM aimed at proposing detailed research on those gaps in order to gain competitive advantages for future studies. Methodology: First, this work applies the keyword GHRM and